2004
DOI: 10.1016/s0968-8080(04)24136-2
|View full text |Cite
|
Sign up to set email alerts
|

The Skilled Attendance Index: Proposal for a New Measure of Skilled Attendance at Delivery

Abstract: Increasing the proportion of deliveries with skilled attendance is widely regarded as key to reducing maternal mortality and morbidity in developing countries. The percentage of deliveries with a health professional is commonly used to assess skilled attendance, but measures only the presence of an attendant, not the skills used or the enabling environment. To supplement currently available information on the presence of an attendant at delivery, a method to measure the extent of skilled attendance at delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 10 publications
1
47
0
Order By: Relevance
“…Furthermore, skilled attendance (or skilled care) at birth connotes delivery in an "enabling environment" with access to emergency obstetric care if required. 27 We therefore felt that place of delivery was a more appropriate variable to include in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, skilled attendance (or skilled care) at birth connotes delivery in an "enabling environment" with access to emergency obstetric care if required. 27 We therefore felt that place of delivery was a more appropriate variable to include in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those from other studies in African countries and the Dominican Republic, Jamaica and Ecuador. [8][9][10][11][12][13][14][15]17,18 Studies have consistently shown a lack of systematic monitoring of maternal or foetal signs during labour or progress of labour, 8,[10][11][12][13]15,17 low or incorrect use of the partograph, 13,15,[17][18][19][20] and poor postpartum care for both mother and baby. 8,11,12,15 The low technical performance in terms of monitoring of labour is perhaps not surprising given the extremely short length of stay of the women in the delivery ward.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not construct average performance indicators by summarising the number of cases fulfilling all criteria. 10,17,41 The main reason for not computing an average index was that the relative importance of each individual indicator is not known (e.g. is monitoring the foetal heart rate more or less important than measuring uterine height?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, women's reports of the health professionals attending delivery may be inaccurate. 32 However, this limitation is less relevant in the Indonesian context, where birth attendants are usually midwives or doctors, than in countries where traditional birth attendants are common. Second, estimates of maternal deaths produced by the capture-recapture method are likely to be less biased than the crude death count based on two informant networks, but there may still have been some bias.…”
Section: Researchmentioning
confidence: 99%